O teatro do oprimido e a flor da permacultura na educação ambiental - Campos, Priscilla Teixeira (2014)
This study seeks to enter the Theatre of the Oppressed and the Permaculture Flower as potentializer methodology of Environmental Education experiences of a new meaning for young people from diverse communities that make up the Collective Youth Movement in Sergipe. The symbolic union of perceptive and sensitive fields aims to broaden the knowledge of the problems in environmental dimensions within that collective. The methodological development of this qualitative research draws on action research through thematic theatrical workshops, covering the methodology described by Augusto Boal in Theatre of the Oppressed, Theatre Games and Improvisation Theatre. Uses the concept of sustainability according to the vision of permaculture perspective of the sensitive environmental education, critique, dialogic, experiential and participatory. Data collection was conducted through questionnaires, interviews, wheels conversation and participant observation. Paintings, sculptures and individual and collective, 4 songs and 1 piece of forum theater on the pesticide issue as the problem - insertion case: many aesthetic materials such as were created. The results include 200 h of fieldwork, 1 workshop in character immersion for 8 days with 32 young people from the Youth Movement Collective in various localities of the state of Sergipe. The piece collectively created by young people was presented 16 times and 1 time in the state at the National Congress of Peasants in Brasilia/DF. People between 1183 and oficinandos audience were mobilized.